Go Camping - Frost, Maddie (New York Viking Children's Books, 2023)
"Best friends, Albert and Pickles, are going camping for the first time and Albert must find a way to help Pickles enjoy the wilderness while they reunite a lost baby koala with its mother"--
Ages 6-9 years.
Grades 2-3.
111475
Keywords: Camping -- Comic books, strips, etc. -- Juvenile fiction; Best friends -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Wombats -- Comic books, strips, etc. -- Juvenile fiction; Koala -- Comic books, strips, etc. -- Juvenile fiction; Graphic novels; Action and adventure comics